Sikap Toleransi Beragama Kalangan Siswa SMA di Banda Aceh - Safrilsyah Safrilsyah; Mauliana Mauliana (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2015)
The purpose of this study is to describe the attitude of religious tolerance among higher school students in Banda Aceh. How higher school students from different religions express religious tolerance and how is the students’ tolerance formed. This research uses descriptive research method, which is conducted in two higher schools (SMU) in Banda Aceh; State higher School of No Three (SMU No. 3) and Private higher school of (SMU) Methodist, from March to August 2013. This research uses purposive sampling in collecting sample from all higher school students in both schools. Eight students consisting of four Muslims and the rest are not Muslims represent the sample. They were interviewed and directly observed. This study indicates that the students’ attitude in interfaith relationship at schools is flexible. From institutional policy, Both school equally treat students of both psychological and learning needs without distinction. Students also express respect to each other and to any kind of differences, acknowledge and allow the manifestation of diverse religious practices and rights. The students do not allow the differences among them become barrier in friendship and other social relationship.